2011
DOI: 10.1152/ajpendo.00108.2011
|View full text |Cite
|
Sign up to set email alerts
|

O-linked β-N-acetylglucosamine supports p38 MAPK activation by high glucose in glomerular mesangial cells

Abstract: Hyperglycemia augments flux through the hexosamine biosynthetic pathway and subsequent O-linkage of single β-N-acetyl-d-glucosamine moieties to serine and threonine residues on cytoplasmic and nuclear proteins (O-GlcNAcylation). Perturbations in this posttranslational modification have been proposed to promote glomerular matrix accumulation in diabetic nephropathy, but clear evidence and mechanism are lacking. We tested the hypothesis that O-GlcNAcylation enhances profibrotic signaling in rat mesangial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 92 publications
(201 reference statements)
8
44
1
Order By: Relevance
“…While there are several members of the MAP3K family that can induce p38 activation, we have shown that ASK1 plays a nonredundant and essential role in activating p38 in the diabetic kidney. This is consistent with a role for ASK1 in high glucose-induced p38 activation in cultured glomerular mesangial cells (36) and the various stresses present in diabetes (e.g., oxidative stress, endoplasmic reticular stress, hyperglycemia, and angiotensin II) that are known to activate ASK1/p38 signaling (37). However, activation of p38 MAPK signaling can operate independent of ASK1 in kidney cells as shown by the unaltered lipopolysaccharide and interleukin-1-induced p38 activation and biological responses seen in Ask1 2/2 tubular epithelial cells (4).…”
Section: Diabetesdiabetesjournalsorgsupporting
confidence: 88%
“…While there are several members of the MAP3K family that can induce p38 activation, we have shown that ASK1 plays a nonredundant and essential role in activating p38 in the diabetic kidney. This is consistent with a role for ASK1 in high glucose-induced p38 activation in cultured glomerular mesangial cells (36) and the various stresses present in diabetes (e.g., oxidative stress, endoplasmic reticular stress, hyperglycemia, and angiotensin II) that are known to activate ASK1/p38 signaling (37). However, activation of p38 MAPK signaling can operate independent of ASK1 in kidney cells as shown by the unaltered lipopolysaccharide and interleukin-1-induced p38 activation and biological responses seen in Ask1 2/2 tubular epithelial cells (4).…”
Section: Diabetesdiabetesjournalsorgsupporting
confidence: 88%
“…Indeed, activation of p38 mapk by the HBP has been reported in mesangial cells, leading to PAI-1 gene expression. 31 In the present study we detected a transient activation of p38 mapk by GlcN, which was potentiated There are studies showing that p38 mapk activates OGT in the HBP, leading to enhanced O-GlcNAcylation of proteins. 30 It is unlikely, however, that in the present experimental setting, TNF-α enhances GlcN-induced PAI-1 expression through augmentation of increased OGT activity, because our previous study showed no further increase in O-GlcNAcylation of cellular proteins in endothelial cells exposed to TNF-α, 38 although O-GlcNAcylation of certain proteins could not be fully excluded.…”
Section: Discussionsupporting
confidence: 61%
“…30 Conversely, O-GlcNAc seems also to be able to activate p38 mapk. 16, 31 The aim of the present study was to investigate the critical role of p38 mapk in GlcN-induced PAI-1 expression and eNOS uncoupling in endothelial cells and in isolated mouse aortas.…”
mentioning
confidence: 99%
“…While the above studies were performed in hepatocytes, subsequent studies in a model of myocardial damage demonstrated that catalase mRNA levels were augmented above baseline following inhibition of O-GlcNAcase (PUGNAc), while overexpression of O-GlcNAcase reduced baseline catalase mRNA levels (Ngoh et al 2011). Notably, in contrast to the studies discussed here, O-GlcNAc is thought to promote ROS generation in models of hyperglycemia and glucose toxicity (Goldberg et al 2011), although the molecular basis for this paradox remains to be defined (Lima et al 2012). …”
Section: Calcium Homeostasismentioning
confidence: 69%